2023
DOI: 10.1186/s13018-023-03687-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of SPECT/CT in painful, noninfected knees after knee arthroplasty: a systematic review and meta-analysis—a diagnostic test accuracy review

Abstract: Purpose The aim of this systematic review was to present the current evidence on the clinical use of single-photon emission computed tomography/computed tomography (SPECT/CT) in the evaluation of noninfected painful knees after knee arthroplasty. Methods Embase, PubMed, Google Scholar, Ovid, Scopus, Science Direct and the Cochrane Database of Systematic Reviews were searched from database inception to May 2022 following the PRISMA guidelines. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Their research highlighted that SPECT/CT stands out as the most accurate diagnostic tool. Additionally, a more recent analysis by Anzola et al focused on the effectiveness of SPECT/CT in identifying pain sources in patients with noninfected knees postarthroplasty, revealing an overall sensitivity of 0.86 (95% CI: 0.79-0.93) and specificity of 0.90 (95% CI: 0.79-0.96) [3]. Our review builds upon these prior studies by offering an updated, comprehensive evaluation of both nuclear and nonnuclear imaging modalities, specifically concerning the diagnostic accuracy for aseptic loosening in knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research highlighted that SPECT/CT stands out as the most accurate diagnostic tool. Additionally, a more recent analysis by Anzola et al focused on the effectiveness of SPECT/CT in identifying pain sources in patients with noninfected knees postarthroplasty, revealing an overall sensitivity of 0.86 (95% CI: 0.79-0.93) and specificity of 0.90 (95% CI: 0.79-0.96) [3]. Our review builds upon these prior studies by offering an updated, comprehensive evaluation of both nuclear and nonnuclear imaging modalities, specifically concerning the diagnostic accuracy for aseptic loosening in knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Anzola et al recently evaluated the role of SPECT/CT in painful noninfected knees. Despite variations across studies, their review concluded that SPECT/CT exhibits high sensitivity and specificity in accurately diagnosing various knee conditions, including loosening [3].…”
Section: Introductionmentioning
confidence: 99%